Influencia del estado de conservación del bosque húmedo tropical sobre las comunidades de himenópteros parasitoides. - Paccha Guamán, Yohanna Alexandra (2017)
The tropical Andes is the richest and most diverse region in the world from a biological point of view, but the current economic development, technological processes, exploitation of natural resources, expansion of the agricultural frontier and accelerated population growth are generating extreme changes in forests vegetation and wildlife, affecting the ecosystems functioning, and leading to the loss of biodiversity. In the current study, the influence of the conservation status of the tropical humid forest on the assemblages of parasitoid Hymenoptera in the Province of Zamora Chinchipe was evaluated. Malaise traps were used for collecting the specimens, which were placed in Copalinga, Numbami and El Padmi stations, in three areas under different conservation levels: primary forest; forest in recovery and disturbed forest. Three superfamilies of parasitoid Hymenoptera were selected for the study: Ichneumonoidea, Chalcidoidea and Evanoidea, and those specimens belonging to these three superfamilies were identified to the family level. During the sampling, 1286 specimens were collected belonging to nine families. From these results, Ichneumonidae and Braconidae with 643 and 451 individuals respectively were the most abundant families, and together with the families Chalcididae, Evaniidae and Pteromalidae were constant during the sampling. We also found some families that were only recorded in certain areas, such as Perilampidae and Eupelmidae in the well-conserved areas, and Eurytomidae in the disturbed areas, which could be proposed as indicative families of those conservation levels. Regarding the statistical analysis of the abundance of the families according to the degree of disturbance, Braconidae was the only family that presented statistically significant differences, being the abundance of the forest in recovery significantly lower than the abundance recorded in the primary forest.